Are we really measuring empathy? Proposal for a new measurement framework. (December 2017) - Coll, Michel-Pierre; Viding, Essi; Rütgen, Markus; Silani, Giorgia; Lamm, Claus; Catmur, Caroline; Bird, Geoffrey
Highlights: Empathy is currently defined as sharing the state of another. This definition conflates the identification and the sharing of another's state. Describing change or impairment in empathy therefore lacks specificity. We show how this can be problematic for popular paradigms in social neuroscience. And propose an alternative measurement framework to resolve. Abstract: Empathy – currently defined as the sharing of another's affective state – has been the focus of much psychological and neuroscientific research in the last decade, much of which has been focused on ascertaining the empathic ability of individuals with various clinical conditions. However, most of this work tends to overlook the fact that empathy is the result of a complex process requiring a number of intermediate processing steps. It is therefore the case that describing an individual or group as 'lacking empathy' lacks specificity. We argue for an alternative measurement framework, in which we explain variance in empathic response in terms of individual differences in the ability to identify another's emotional state ('emotion identification'), and the degree to which identification of another's state causes a corresponding state in the self ('affect sharing'). We describe how existing empathy paradigms need to be modified in order to fit within this measurement framework, and illustrate the utility of this approach with reference to examples from both cognitive neuroscience and clinical psychology.